Video Animation: Improving Older Adults Patients Knowledge and Motivation Related to Hypertension Diet - Gusti Ayu Kade Budiarti; Sri Susanty; Ruslan Madjid; Ramadhan Tosepu (Jurnal Keperawatan Indonesia)
Hypertension is a dangerous medical condition that can increase the risk of heart, brain, and renal problems, among other issues. A balanced diet is an essential hypertension control intervention. This study seeks to examine the efficiency of employing animation media to explain the application of diets that prevent hypertension and boost the understanding and motivation of senior patients at Bahteramas Regional General Hospital. In both the control and intervention groups, a quantitative-quasi-experimental design was adopted, with pre-test and post-tests. Data was obtained via questionnaires from 92 respondents chosen using a purposive sampling approach, with 46 in the intervention group from the cardiac clinic and 46 in the control group from geriatric clinic. The data were analyzed using the paired t-test. The findings of the study indicated that patient knowledge increased significantly (p = 0.007) in the cardiac clinic following the administration of animation media, whereas in the geriatric clinic, no impact was observed (p = 0.000). Patient motivation increased significantly in the cardiac clinic following the administration of animation media (p = 0.003) and in the geriatric clinic in the absence of intervention (p = 0.000). There was no significant difference between the two groups in pretest knowledge (p = 0.666) and motivation (p = 0.747); however, there were significant differences in posttest knowledge (p = 0.015) and motivation (p = 0.026). Patient knowledge was affected by animation media in the cardiac clinic (p = 0.007) and without therapy in the geriatric clinic (p = 0.000). Incorporating animated educational content into routine patient counseling and health education programs can be beneficial in the future.